The Customer Pressure And Organizational Commitment On Environmental Performance Mediating Proactive Enviromental Strategies - Sibarani, Lisbeth; Genoveva, Genoveva (Archives of Business Research, 2019)
The survey found that more than 6 in 10 consumers in Indonesia (64%) are more willing to pay extra for products and services that come from companies who are committed to making positive social and environmental impact. This is contrasts from the results of the pre-survey which showed that 5 companies which applied the environmental system management, showed that they found it difficult to enhance their environmental performance due to the lackness of the organizational commitment. This study aims to know how corporate strategies that implement green marketing can affect to the environmental performance. This study used quantitative approach. The population in this research are 50 companies listed in the Jakarta Stock Exchange which has implemented environmental management system. The data has been processed by using SmartPLS software version 3.0. The result conclude that there are four hypotheses accepted, they are : Customer Pressure has positive impact towards Proactive Environmental Strategies; Organizational Commitment has positive impact towards Proactive Environmental Strategies; Proactive Environmental Strategies has positive impact towards Environmental Performance and Organizational Commitment has positive impact towards Environmental Performance. While the result showed that Customer Pressure has negative impact towards Environmental Performance. Nevertheless, each hypotheses has significant impact.